2019
DOI: 10.1042/bsr20182193
|View full text |Cite|
|
Sign up to set email alerts
|

MUC1 gene silencing inhibits proliferation, invasion, and migration while promoting apoptosis of oral squamous cell carcinoma cells

Abstract: The aim of the present study is to investigate the role of RNA interference in the inhibition of MUC1 gene expression in occurrence and metastasis of oral squamous cell carcinoma (OSCC) and its in-depth mechanisms. The OSCC and normal oral mucosa tissues, as well as normal oral epithelial cell line HOK and OSCC cell line SCC-4, Cal-27, TSCCA, Tca8113 were obtained to detect the expression of MUC1. Slug expression in OSCC and normal oral mucosa tissues was also determined. The OSCC cells were grouped to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Besides, mucin 1 (MUC1), a tumor driver gene in our study, is a membranebound protein whose gene expression is highest in the respiratory, digestive, and reproductive systems, and plays a role in cell growth, differentiation, and cell signal transduction (35)(36)(37). In oral squamous cell carcinoma (OSCC), silencing MUC1 can reduce the expression of Slug, thereby inhibiting tumor cell proliferation, inhibiting DNA replication, and inducing OSCC cell apoptosis (38). In addition, MUC1 can also be used as a useful marker for predicting poor prognostic factors for 5-year survival outcome after radical esophageal squamous cell carcinoma resection (39).…”
Section: Discussionmentioning
confidence: 94%
“…Besides, mucin 1 (MUC1), a tumor driver gene in our study, is a membranebound protein whose gene expression is highest in the respiratory, digestive, and reproductive systems, and plays a role in cell growth, differentiation, and cell signal transduction (35)(36)(37). In oral squamous cell carcinoma (OSCC), silencing MUC1 can reduce the expression of Slug, thereby inhibiting tumor cell proliferation, inhibiting DNA replication, and inducing OSCC cell apoptosis (38). In addition, MUC1 can also be used as a useful marker for predicting poor prognostic factors for 5-year survival outcome after radical esophageal squamous cell carcinoma resection (39).…”
Section: Discussionmentioning
confidence: 94%
“…28 Juan et al have shown that miR-489 served for an anti-proliferative and pro-apoptotic maker in CC cells, 29 and miR-148a was used as a novel target to suppress the progression of CC. 30 Interestingly, we found that miR-19a-3p was highly expressed in CC tissues and cells but its expression was reduced after baicalein treatment in CC cells, which demonstrated that the biological function of baicalein in CC might be related to the downregulation of miR-19a-3p. Our reverted assays subsequently exhibited that the overexpression of miR-19a-3p recovered the regulation of baicalein in CC cells, validating that baicalein functioned in CC cells via the expression inhibition of miR-19a-3p.…”
Section: Dovepressmentioning
confidence: 70%
“…Due to the higher expression of MUC1 in OSCC than in normal mucosal tissues, it is considered a reliable biomarker for the diagnosis of OSCC. Silencing the MUC1 gene could induce apoptosis and inhibit the proliferation, invasion, migration and EMT of OSCC cells 123 , 124 . T]his membrane-localized glycoprotein is overexpressed and aberrantly glycosylated in most epithelial cancers 125 , and the aberrant glycosylation of MUC1 might result in the shortening of the sugar chain, causing the exposure of hidden antigens; the hidden antigens usually have peptidic and carbohydrate properties, making the MUC1 epitope tumor-specific 126 .…”
Section: Aberrant Muc1 Glycosylation In Hnsccmentioning
confidence: 98%